Ona-tili va adabiyoti darslarida o‘quvchilarning nutqiy ko‘nikmalarini rivojlantirishda tez aytishlarining o‘rni - Xaytboyev Boburjon Xamzayevich (Euro Asian Journal Publishing, 2023)
This article explores the significant role of students in enhancing their speech skills within the context of native language and literature lessons. It highlights the importance of active participation, self-expression, and critical thinking in fostering language proficiency and literary appreciation. By emphasizing student engagement, educators can create a dynamic learning environment that cultivates effective communication and nurtures a love for language and literature
Keywords: nutq qobiliyatlari; ona tili; adabiyot darslari; og'zaki muloqot